Motivasi Belajar Anak dalam Konteks Kehidupan Pedesaan: Studi Kualitatif di MI Tarbhiyatus Sibyan Desa Jelun - Kirana, Novrinda Gatri; Syaifullah, Khalid; Ridwan, Ahmad; Jacky, M. (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
This study aims to understand the learning motivation of children at Madrasah Ibtidaiyah Tarbhiyatus Sibyan in Jelun Village, Banyuwangi Regency, by examining how family background and social environment shape their perspectives on education and the future. The study employs a qualitative method with a case study approach, utilizing participatory observation and direct conversations during teaching activities. The findings indicate that children's learning motivation is influenced by family habitus, emotional stability, and the social capital available in their daily lives. Children from families with strong educational support tend to have a clear future orientation, while children from non-harmonious or less stable families often show apathetic attitudes toward school and choose to work after graduating from the MI. In addition, the study found the existence of a pseudo-identity construction in some students as a form of psychological compensation due to the lack of parental involvement. This analysis is reinforced by Pierre Bourdieu's habitus theory and Bronfenbrenner's ecological theory, which show that learning motivation is not only born from individual willingness but also from the relationship between the family environment, school, and village social structures. This study concludes that differences in children's learning motivation at MI Tarbhiyatus Sibyan are closely related to each child's social conditions and life experiences. The results of this study are expected to serve as a reference for schools and communities to strengthen social and educational support for children in rural areas.